2022
DOI: 10.1152/ajplung.00052.2022
|View full text |Cite
|
Sign up to set email alerts
|

CD14-positive extracellular vesicles in bronchoalveolar lavage fluid as a new biomarker of acute respiratory distress syndrome

Abstract: Recent studies have indicated that extracellular vesicles (EV) may play a role in the pathogenesis of Acute Respiratory Distress Syndrome (ARDS). EV have been identified as potential biomarkers of disease severity and prognosis in other pulmonary diseases. We sought to characterize the EV phenotype within ARDS patient broncho-alveolar lavage fluid (BAL), and to determine whether BAL EV could be utilized as a potential biomarker in ARDS. BAL was collected from sepsis patients with and without ARDS, and from eso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…Recent studies have found that EVs with CD14 + in BALF can also serve as a new biomarker for ARDS. Elevated counts of EVs with CD14 + /CD81 + in BALF of patients with sepsis-associated ARDS are associated with the increased mortality of patients with ARDS . SCAP usually leads to high mortality in ARDS.…”
Section: Role Of Exosomal Mirnas In the Diagnosis Of Alimentioning
confidence: 99%
“…Recent studies have found that EVs with CD14 + in BALF can also serve as a new biomarker for ARDS. Elevated counts of EVs with CD14 + /CD81 + in BALF of patients with sepsis-associated ARDS are associated with the increased mortality of patients with ARDS . SCAP usually leads to high mortality in ARDS.…”
Section: Role Of Exosomal Mirnas In the Diagnosis Of Alimentioning
confidence: 99%
“…In fact, EVs were more abundant in BALF of ARDS patients compared with patients with hydrostatic oedema and had greater pro-coagulant activity, mediated by a higher expression of TF [ 107 ]. Compared with septic patients without lung involvement, patients with sepsis-related ARDS had higher number of CD14+/CD81+ monocyte-derived EVs in BALF and this signature was associated with dismal outcome [ 108 ].…”
Section: Role Of Extracellular Vesicles In Sepsis-associated Ardsmentioning
confidence: 99%
“…These data were expanded in a study showing that patients who underwent esophagectomy and further developed ARDS had higher concentration of endothelial-derived CD31 + EVs in BALF compared with healthy subjects. Considered together, these studies suggest that the secretome of monocytes and ECs play a role in ARDS pathogenesis and in identifying those patients who are at risk of developing the syndrome [ 108 ]. Table 3 showed a synthesis of clinical trials assessing the safety and efficacy of intravenous treatment with MSCs and MSC-derived EVs in human subjects with ARDS.…”
Section: Role Of Extracellular Vesicles In Sepsis-associated Ardsmentioning
confidence: 99%
“…Extracellular vesicles from monocytes were found in the bronchoalveolar lavage (BAL) of septic patients and were shown to be significantly associated with ARDS and the mortality of patients ( 61 ). A significant release of Exos was observed in an experimental in vitro setting of LPS-treated alveolar macrophages, which induces lung inflammation and was significantly ameliorated via Exo downregulation due to hydrochloride hydrate treatment ( 62 ).…”
Section: Introductionmentioning
confidence: 99%